Clinical study of perforations among patients at a tertiary care hospital - S. V., Mahesh; Reddy, Dilip Kumar; P. K., Hota (International Surgery Journal, 2018)
Background: Non-traumatic gastrointestinal perforations have received far less attention in the recent medical literature than inflammations, tumoral or traumatic lesions of solid abdominal organs. The objective is to study perforations among patients at a tertiary care hospital. Methods: Patients diagnosed as non-traumatic perforations of the internal organs as diagnosed by authors were planned to be included for the present study. Diagnosis was based on history, clinical examination, and required investigations. All such patients were included in the present study that was enrolled for the present study during the study period. Such 50 patients could be studied. Non-traumatic perforation with regard to age, sex, causes, clinical presentation, diagnostic modalities required was evaluated. Results: Most common age group involved is in 3rd to 4th decade in the present study. Male preponderance (82%) was seen; with a male to female ratio was 4.6:1. The time lapse between onset of symptoms and presentation at the hospital was more than 24 hours in 24% of the study population. Abdominal pain was the most consistent symptom and was seen in 100% of the study population in the present study followed by vomiting (52%) and fever (46%). Distended abdomen was seen in 46% of study population in the present study. Tenderness was seen in all the cases and is more prominent at the site of perforation. Guarding/rigidity and absent bowel sounds were seen in 92% of the study population. Sensitivity of imaging in detecting gas under diaphragm was 72% by USG abdomen and 80% by plain radiography. Conclusions: Risk factors for increased morbidity and mortality in the present study include older age group, delayed presentation and features of shock.